EVALUATION OF TOXIOLOGICAL INDICATORS OF MONTHMORRILLONITE CLAY FOR THE PURPOSE OF USING THEM AS ALUMOSILICATE SOBENT AGAINST THE NEGATIVE EFFECT OF MYCOTOXINS ON THE BODY OF ANIMALS AND BIRDS - Montayeva, N.S. (Ғылым және білім=Наука и образование=Science and education., 2021)
The article presents the results of scientific and experimental research on the creation of organic-mineral ceramic biomaterial for biofilters used in the conditions of growing sturgeon fry using a closed water supply. The information on the analysis of the main stress factors leading to the most frequent diseases of sturgeon fish in closed water supply conditions is presented. To prevent the impact of unfavorable conditions or reduce them to a minimum, the results of studies on the creation of a new organic-mineral ceramic biomaterial based on environmentally friendly natural raw materials for biofiltration and water purification in conditions of closed water supply are presented. It has been established that the proposed organomineral ceramic biomaterial serves as biofilters both as water purification and as an element of prophylaxis against fish diseases.В статье представлены результаты научно-экспериментальных исследований по созданию органоминерального керамического биоматериала для биофильтров используемых в условиях выращивания мальков осетровых рыб по замкнутому водоснабжению. Приведены сведения по анализу основных стресс - факторов приводящие к наиболее частым заболеваниям осетровых рыб в условиях замкнутого водообеспечения. Для предотвращения воздействия неблагоприятных условий или снижение их до минимума представлены результаты исследований по созданию нового органоминеральный керамического биоматериал на основе экологический чистой природных сырьевых материалов для биофильтрации и очистки воды в условиях замкнутого водообеспечения. Установлено, что предлагаемый органоминеральный керамический биоматериал служат биофильтрах как в качестве очистки воды, а так же как элемент профилактики против заболеваний рыб.
Keywords: научный журнал; отечественное издание; периодическое издание; журнал кксон; рыбное хозяйство; осетровые рыбы; мальки; очистка воды; биофильтрация; замкнутое водоснабжение